Vozes de “Marias”: transformação social proporcionada pela gastronomia à mulheres/mães e suas famílias em situação de vulnerabilidade atendidas pelo IPREDE - Braga, Eveline Vasconcelos Sales de Castro (2024)
The present research addresses Social Gastronomy and the development generated, focusing on the history and actors of this practice in an institution that helps vulnerable families, highlighting the multiplicity of possible approaches. Issues such as poverty, food deprivation, and lack of opportunities drove the investigation, considering the problems of hunger, food waste, and income generation. The research emphasizes the importance of empowering women, aiming not only for their personal growth but also positively impacting various other objectives, such as promoting food and nutritional security and raising awareness of a sustainable food culture. The study questions how such projects contribute to socioeconomic development, female empowerment, food culture, and combating hunger in vulnerable families and communities served by the Institute of Early Childhood (IPREDE). Objectives include the analysis of the social impact of Gastronomy on the lives of women/mothers and their families, as well as the application of sustainable practices to combat hunger in communities assisted by the mentioned institution. Specific objectives encompass the description and analysis of the Realimenta, TransforMaria, Prato Cheio, and Conversas de Cozinha projects, conducting a socioeconomic diagnosis of participants, analyzing the actions of the TransforMaria project as a transformation tool, studying graduates and their impacts, evaluating the impact of chefs teaching in the TransforMaria project, analyzing the sustainable actions of the Prato Cheio project in combating hunger, and examining the impact and awareness of participants in the Conversas de Cozinha project regarding food culture and the full use of food. The methodology used was the Life History, with the interview as the data collection instrument. A mobile device was used for video recording the interviews. Data analysis and interpretation were conducted using the thematic analysis method. Four categories and their subcategories emerged in the data analysis: a) learning; b) self-confidence; c) income generation; d) culture; e) transformation; f) food insecurity; g) food culture. Among other results, the subjects pointed to an improvement in the quality of life through employability and entrepreneurship, the transformation of lives generated social responsibility, awareness about food waste and the full use of food, the mitigation of hunger, and the enrichment of food culture developing a new vision about food.